Combination of trypsin, rutoside, bromelain and diclofenac sodium in the management of internal derangement of temporomandibular joint: A randomized clinical trial - Prashant Gupta; Shantala R Naik; L Ashok; R Poornima; Ranjani Shetty (Wolters Kluwer Medknow Publications, 2020)
Background: Internal derangement of temporomandibular joint (TMJ) is a chronic disease which causes a considerable amount of pain and reduced chewing ability and thus compromising patients eating ability and lifestyle. Aims: This study was carried out to evaluate the clinical effectiveness of enzymes like trypsin, rutoside, bromelain, and diclofenac combination against the use of diclofenac alone in the treatment of internal derangement (ID) of TMJ. Settings and Design: This study was done in the OPD of Oral Medicine and Radiology department at dental institute and is a randomized case-controlled clinical trial. Methods and Materials: 30 subjects were enrolled in the study by simple random sampling and were diagnosed clinically as ID and radiographically screened. They were divided into 2 groups of 15 each. Group I was given oral diclofenac sodium and group II was given an oral combination of trypsin, rutoside, bromelain, and diclofenac sodium for a span of 14 days. Statistical Analysis: It was done by comparing the mean, median, and standard deviation of each variable. Comparative analysis was done using the Mann-Whitney U test, Friedman's test, Chi-square test, Student's t-test, and ANOVA to find the P- value and confidence interval. Results: Both the groups had reduced pain, improved chewing ability and mouth opening, and reduction in joint noise and jerky mandibular movements. Group I, patients had better results when compared to group I and the differences were highly significant. Conclusion: We recommend the use of a combination of enzymes and diclofenac for the management of ID of TMJ.